12. Sensitivity and predictive value of OCT and VEP in multiple sclerosis. Issue 4 (April 2016) - Di Maggio, G.; Santangelo, R.; Guerrieri, S.; Ferrari, L.; Vitali, F.; Medaglini, S.; Rodegher, M.; Colombo, B.; Moiola, L.; Del Carro, U.; Martinelli, V.; Comi, G.; et al.
Abstract : Aim of the study was to evaluate the role of optical coherence tomography (OCT) and visual evoked potentials (VEPs) in patients with multiple sclerosis (MS), on 121 consecutive subjects with MS. Of 242 eyes, 166 had no previous history of optic neuritis (ON), 22 had a single recent ON episode (<3 months); 54 had chronic ON (at least 1 episode >3 months before). All patients underwent assessment of EDSS, OCT retinal nerve fiber layer (RNFL) thickness and VEP (checkerboard, size 15′); 77 subjects underwent a second EDSS (EDSS2) evaluation after a mean time of 2 ± 0.69) years (median EDSS 2, range 0–7). In eyes with recent ON, the sensitivity of OCT was 38.9% with a higher sensitivity of VEP (77.3%; McNemar p  < 0.02). In eyes with chronic ON, no significant difference was found between OCT (68.5%) and VEP (81.5%) sensitivity. In asymptomatic eyes, VEPs had a higher sensitivity (31.7%) vs OCT (19.9%; p  = 0.005); VEP/OCT combined detected abnormalities in 39.2%. In follow up evaluation, OCT alterations were associated with development of disability after 2 years ( p  = 0.013). VEP alterations did not predict future disability development neither in patients with previous ON nor in those without. The present findings confirm a higher sensitivity of VEPs in the subacute phases of optic neuritis (less than 3 months) and in asymptomatic eyes. In eyes without previous optic neuritis, early asymptomatic OCT abnormalities are associated with short-term worsening of disability. Further longitudinal studies are needed to confirm our findings.